2007
DOI: 10.1007/s00280-007-0609-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effects of rapamycin as a single agent and in combination with carboplatin and paclitaxel in head and neck cancer cell lines

Abstract: Our results show that rapamycin displays antiproliferative effects and induces apoptosis in HNSCC cell lines, cellular effects being more potent in cells that do not express BCL2 and MDR1. Additive and synergistic effects were observed when rapamycin was combined with carboplatin and paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 25 publications
2
63
1
1
Order By: Relevance
“…In light of the cell-cycle relationship we uncovered, this may account for why more potent synergistic effects were not observed. Similar combinatorial benefit has been reported for rapamycin with these same cytotoxic agents in breast, hepatocellular carcinoma, and head and neck cancer lines (34)(35)(36).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In light of the cell-cycle relationship we uncovered, this may account for why more potent synergistic effects were not observed. Similar combinatorial benefit has been reported for rapamycin with these same cytotoxic agents in breast, hepatocellular carcinoma, and head and neck cancer lines (34)(35)(36).…”
Section: Discussionsupporting
confidence: 73%
“…The mTOR inhibitor rapamycin has been shown to potentiate the cytotoxic activity of multiple chemotherapeutic agents in a number of cancer cell types in vitro (25,34,35). Therefore, an important objective of this study was to determine whether ridaforolimus enhanced the efficacy of chemotherapeutics commonly used in sarcoma and endometrial cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In tumours addicted to this growth factor stimulation, chemotherapy combined with mTOR inhibition has shown synergistic anti-tumour effects. For example, data have shown that rapamycin and everolimus can enhance the antitumour activity of paclitaxel (O'Reilly et al, 2003;Mondesire et al, 2004;Faried et al, 2006;Aissat et al, 2007;Haritunians et al, 2007) in a manner related in occurrence and extent to the tumour, dose, and interestingly, the sequence of administration of the mTOR inhibitor and paclitaxel (O'Reilly et al, 2003;Mondesire et al, 2004;Faried et al, 2006;Aissat et al, 2007). In vitro, paclitaxel treatment before mTOR inhibition produced greater enhancement of apoptosis than treatment after or simultaneously with the mTOR inhibitor, which may reflect a conflict between the slowing of the cell cycle through the G 1 -S transition by mTOR inhibition and the requirement that cells be in G 2 -M transition for paclitaxelinduced apoptosis (Mondesire et al, 2004;Aissat et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study with cervical cancer cells, treatment with rapamycin preceding paclitaxel produced the more favourable result (Faried et al, 2006), suggesting that sequence dependency may be influenced by different mechanisms in other types of cancer. Inhibition of protein synthesis by mTOR inhibition may additionally contribute to apoptosis by preventing repair of paclitaxel-induced cell damage (Aissat et al, 2007). The extent to which sequence dependency translates in vivo is also not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Everolimus (Afinitor Ò , Novartis Pharmaceuticals Corporation, East Hanover, NJ), an mTORC1 inhibitor, sensitizes cancer cell lines to platinum and taxane CT [63]. Despite much interest in the use of induction CT, well-designed studies have found no improvement in overall survival with induction CT followed by chemoradiation versus chemoradiation alone (DeCIDE study [64], PARADIGM study [65]).…”
Section: Mtor Inhibitionmentioning
confidence: 99%